Efektivitas Penyampaian Pesan Moral dalam Film Siksa Neraka pada Penonton Remaja - Setiawan, Laurencia Michelle; Sukendro, Gregorius Genep (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
This research examines the role of mass communication in shaping the psychological responses of teenagers to the moral messages in the film Siksa Neraka. Using a qualitative approach, data were collected through interviews and film text analysis to understand the emotional experiences of the audience. The results show that this film not only serves as entertainment but also as an educational tool that conveys a strong moral message. Teen viewers showed significant emotional responses, with many of them reflecting on their actions and behavior after watching. The theories used in the research include the Uses and Gratifications Theory, which explains the audience’s selection of media to meet emotional needs; the Mass Communication Theory, which emphasizes the power of films in conveying moral messages; and the Audience Psychology Theory, which analyzes how films trigger the audience’s emotional responses. Additionally, Piaget’s Cognitive Development Theory describes how adolescents’ understanding of films is influenced by their cognitive development stage. In conclusion, Siksa Neraka serves as an effective educational tool and can provoke reflection on the audience’s actions. This research is expected to contribute to communication studies and serve as a guide for filmmakers to create more responsible works. Penelitian ini mengkaji peran komunikasi massa dalam membentuk respons psikologis remaja terhadap pesan moral dalam film Siksa Neraka. Dengan pendekatan kualitatif, data dikumpulkan melalui wawancara dan analisis teks film untuk memahami pengalaman emosional penonton. Hasilnya menunjukkan bahwa film ini tidak hanya berfungsi sebagai hiburan, tetapi juga sebagai alat edukasi yang menyampaikan pesan moral yang kuat. Penonton remaja menunjukkan respons emosional yang signifikan, dengan banyak dari mereka merenungkan tindakan dan perilaku mereka setelah menonton. Teori yang digunakan dalam penelitian ini meliputi Teori Uses and Gratifications yang menjelaskan pemilihan media oleh penonton untuk memenuhi kebutuhan emosional; Teori Komunikasi Massa, yang menekankan kekuatan film dalam menyampaikan pesan moral; dan Teori Psikologi Penonton, yang menganalisis bagaimana film memicu respon emosional penonton. Selain itu, Teori Perkembangan Kognitif Piaget menggambarkan bagaimana pemahaman remaja terhadap film dipengaruhi oleh tahap perkembangan kognitif mereka. Kesimpulannya, Siksa Neraka berfungsi sebagai alat edukasi yang efektif dan dapat memicu refleksi tentang tindakan penonton. Penelitian ini diharapkan memberikan kontribusi bagi studi komunikasi dan panduan bagi pembuat film untuk menciptakan karya yang lebih tanggung jawab.